Preferential treatment moderating role on parental social economic status impact on students achievement in computer studies - Hassan, Olusola; Adetayo, Janet Oyebola; Olurinola, Oluwakemi; Olugbuyi, Olusile (Universitas Negeri Yogyakarta, 2023)
Parental Social Economic Status will continue to change from time to time and there has been inconsistency on its impact on students' academic performance. This study investigated the moderating effect of preferential treatment on the impact of Parental Social Economic Status on students' academic performance in Ogun state. The study used descriptive survey research design with 392 students as sample, selected through multi stage sampling approach. Parental Social economic Status Scale (PSESS, 0.77), Preferential Treatment Scale (PTS0.82) and Students Academic Perfroamnce Proformat were used for data collection. Percentage and regression were used for data analysis. Finding of the study showed that PSES and preferential treatment has significant impact on students academic performance ((F(1,390) = 173.734 P < 0.05, F(1,390) = 7.250 P < 0.05). The combination of PSES and preferential treatment also produced significant outcome ((F(1,389) = 87.956 P < 0.05). The moderating effect of preferential treatment on the impact of PSES on students' academic performance was also significant (t = 12.869, p <0.05). It is concluded that there is significant moderating effect of preferential treatment on impact of PSES on students' academic performance in senior secondary schools in Ogun State